The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/odi.13494
|View full text |Cite
|
Sign up to set email alerts
|

FAK inhibition protects condylar cartilage under excessive mechanical stress

Abstract: Temporomandibular joint disorder (TMD) is a degenerative multifactorial disease. Temporomandibular joint (TMJ) osteoarthritis (OA) is severe form of TMD and characterized by cartilage degradation. Cartilage degradation leads to loss of the extracellular matrix (ECM). Some researchers have suggested excessive mechanical stress as a risk factor for TMJ-OA (Ikeda, Yonemitsu, Takei, Shibata, & Ono, 2014) (Asakawa-Tanne et al., 2015). An optimal level of mechanical stress is necessary for ECM maintenance in cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Thus, it would be predicted that the preclinical mouse model would have lower levels of FAK and pFAK at Tyr397. This is in contrast to reports that mechanical and inflammatory injury of cartilage in the mandible [25], cartilage of the intervertebral disc [60], and skin [13] are associated with an increase in the level of pFAK at Tyr397. Western blot analysis of the whole joint after TMJ OA illustrates the largest increase in FAK and pFAK at Tyr397 in sham control tissues and no significant difference between the TMJ OA and non-surgical control samples.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, it would be predicted that the preclinical mouse model would have lower levels of FAK and pFAK at Tyr397. This is in contrast to reports that mechanical and inflammatory injury of cartilage in the mandible [25], cartilage of the intervertebral disc [60], and skin [13] are associated with an increase in the level of pFAK at Tyr397. Western blot analysis of the whole joint after TMJ OA illustrates the largest increase in FAK and pFAK at Tyr397 in sham control tissues and no significant difference between the TMJ OA and non-surgical control samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, iFAK treatment suppresses MMP13 in a loading independent manner and attenuates matrix proteolysis. This hypothesis is consistent with data from a rat mandibular condyle explant model loaded under static compression with and without FAK inhibitor PF0455487, illustrating FAK dependent suppression of inflammatory biomarkers, MMP13 mediated proteolysis, and TUNEL staining in the chondroblastic and hypertrophic cell layer [25]. The inhibition of pFAK at Tyr397 is also associated with an increase in TGFβ.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“… 321 Pharmacological inhibition of FAK relieved the degradation of articular cartilage of the mandibular condyle under mechanical loading by inhibiting the expression of pro-inflammatory cytokines and ECM-degrading enzymes. 322 Miyauchi and coworkers showed that genetic deletion of the Hic-5 (hydrogen peroxide-inducible clone-5), a focal adhesion mechanosensitive adapter, alleviated the progression of OA through regulation of chondrocyte catabolism induced by mechanical stress. 323 …”
Section: Pathogenic Pathways and Moleculesmentioning
confidence: 99%